Use of conceptual metaphor in Sam Omatseye’s “In Touch” column in The Nation Nigerian newspaper - Atolagbe, Oluwadmilare Daniel; Abdullahi-Idiagbon, Mohammed Sani (Journal of Modern Languages, 2017)
Conceptual metaphors “are abstract structures of thought that function as a conceptual frame in terms of which single lexical items are produced and comprehended” (Muller, 2008). This study is motivated by how a Nigerian newspaper columnist, Sam Omatseye, uses conceptual metaphors to aid in the comprehension of his ideas by the readers. A cognitive semantic approach to metaphor is used as the theoretical framework for this study. Using a stratified sampling method, the study chooses all the February 2015 editions of “In Touch” by Sam Omatseye in The Nation to drive home its point. The study found that Mr Omatseye deploys conceptual metaphors and uses metaphors from several source domains to express his target domains clearly. The paper concludes that studying conceptual metaphors throws additional insights into the transactional function of language and provides a helpful tool for understanding how language can be effectively manipulated to attract readers’ attention.